Investigation of turbulent premixed methane/air and hydrogen-enriched methane/air flames in a laboratory-scale gas turbine model combustor. (6th April 2021) - Liu, Xin; Bertsch, Michael; Subash, Arman Ahamed; Yu, Senbin; Szasz, Robert-Zoltan; Li, Zhongshan; Petersson, Per; Bai, Xue-Song; Aldén, Marcus; Lörstad, Daniel
Abstract: Methane and hydrogen-enriched (25 vol% and 50 vol% H2 -enriched CH4 ) methane/air premixed flames were investigated in a gas turbine model combustor under atmospheric conditions. The flame operability ranges were mapped at different Reynold numbers (Re), showing the dependence on Re and H2 concentrations. The effects of equivalence ratio (Φ), Re, and H2 enrichment on flame structure were examined employing OH-PLIF measurement. For CH4 /air cases, the flame was stabilized with an M shape; while for H2 -enriched cases, the flame transitions to a П shape above a specific Φ. This transition was observed to influence significantly the flashback limits. The flame shape transition is most likely a result of H2 enrichment, occurring due to the increase in flame speed, higher resistance of the flame to the strain rate, and change in the inner recirculation zone. Flow fields of CH4 /air flames were compared between low and high Re cases employing high-speed PIV. The flashback events, led by two mechanisms (combustion-induced vortex breakdown, CIVB, and boundary-layer flashback, BLF), were observed and recorded using high-speed OH chemiluminescence imaging. It was found that the CIVB flashback occurred only for CH4 flames with M shape, whereas the BLF occurs for all H2 -enriched flames with П shape. Highlights: The premixed H2 /CH4 /air flames were studied in a burner with offset-cone swirler. The effects of H2 on flame structure and stability have been demonstrated. Flame shape transition (M to П) occurred at certain Φ only for H2 -enriched cases. The П-shaped flames were found less prone to flashback. Flashback driven by different mechanisms were observed for M- and П-shaped flames.